Parlomacy in Iran’s Foreign Policy - Rahmat Hajimineh; Mohammad Abedi (رهیافتهای سیاسی و بین المللی)
Since the development of the concept of diplomacy and downfall of the traditional ‘dominance’ of government on this concept, parliamentary diplomacy, which roared in concluding decades of the twenty-first century, has been held as an emerging aspect of diplomacy and one of its types. Notwithstanding, parliamentary diplomacy has failed to magnetize substantial investigations. In the recent years, parliamentary diplomacy of the Islamic Consultative Assembly has been on a considerable rise. Included in this are international talks and positions held by chairman of parliament, effective presence in international parliamentary assemblies such as Asian States Inter-Parliamentary Union and Inter-Parliamentary Union (IPU), increased parliamentary friendship groups in more than 100 countries, and continuous consultations offered by parliamentary committees. This is thus questioned that “What is the stance of parliamentary diplomacy in the foreign policy of the Islamic Republic of Iran?” Relying upon the framework provided by examination of the trends ending in parliamentary diplomacy, the present article argues that applications and capacities of parliamentary diplomacy in the foreign policy of the Islamic Republic of Iran are an accepted, growing, and comprehensive—but nascent—issue. In doing so, this research undertakes to investigate development of the concept of diplomacy under rubric of the trends ending in parliamentary diplomacy, delving into indicators of structures, processes, and agendas for understanding those at the helm of diplomacy, the manner to organize diplomacy, and the issues negotiated in the concept of diplomacy over time. Description of applications and differences of parliamentary diplomacy as to other forms of diplomacy is a result of this framework. After the introduction, research’s hypothesis will be tested by comparing the three above-mentioned indicators in parliamentary diplomacy in the foreign policy of the Islamic Republic of Iran. This study has been formulated in a descriptive-analytical form in terms of its methodology.